circVEGFA inhibits apoptosis in porcine ovarian granulosa cells by binding to miR-21-3p and up-regulating TMX4 expression - Xinxin Qin; Jinbi Zhang; Chao Yin; Fan Li; Wenjie Li; Xiaolong Cheng; Xing Du; Qifa Li; Zengxiang Pan (Journal of Ovarian Research)
Abstract Background Follicular atresia is a major determinant of ovarian failure in multiparous sows. Non-coding RNAs (ncRNAs) play an important role in the regulatory mechanisms controlling apoptosis within ovarian granulosa cells (GCs). Methods The circular structure of circVEGFA was validated by RNase R and actinomycin D treatments. The function of circVEGFA during apoptosis in GCs was investigated by si-RNA transfection. Furthermore, competitive binding of circVEGFA and TMX4 to miR-21-3p was confirmed by a dual-luciferase reporter gene assay and co-transfection with their inhibitors or siRNA. Results: In this study, we present a novel circular RNA (circRNA), circVEGFA, which shows significantly reduced expression in atretic follicles (AFs) compared to healthy follicles (HFs). Conclusions The study demonstrates that circVEGFA increases TMX4 expression and inhibits apoptosis in GCs through competitive binding to miR-21-3p. This study contributes to the understanding of circRNA regulation after follicular atresia.